Gray Matter Volume in Different Cortical Structures Dissociably Relates to Individual Differences in Capacity and Precision of Visual Working Memory. (18th April 2020) - Machizawa, Maro G; Driver, Jon; Watanabe, Takeo
Abstract: Visual working memory (VWM) refers to our ability to selectively maintain visual information in a mental representation. While cognitive limits of VWM greatly influence a variety of mental operations, it remains controversial whether the quantity or quality of representations in mind constrains VWM. Here, we examined behavior-to-brain anatomical relations as well as brain activity to brain anatomy associations with a "neural" marker specific to the retention interval of VWM. Our results consistently indicated that individuals who maintained a larger number of items in VWM tended to have a larger gray matter (GM) volume in their left lateral occipital region. In contrast, individuals with a superior ability to retain with high precision tended to have a larger GM volume in their right parietal lobe. These results indicate that individual differences in quantity and quality of VWM may be associated with regional GM volumes in a dissociable manner, indicating willful integration of information in VWM may recruit separable cortical subsystems.